2020
DOI: 10.31895/hcptbn.14.3-4.7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of non-thermal processing techniques on sulfur dioxide and oxygen concentrations in young and aged wines

Abstract: The application of innovative techniques like high hydrostatic pressure (HHP) and high power ultrasound (HPU) for food processing and preservation is one of the current topics in food science. In the enological field, these techniques have been identified as alternative methods for wine microbial stabilization and acceleration of wine aging process. Due to lack of available information about their influence on physicochemical characteristics, the aim of this work was to study the effect of HHP and HPU on sulfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Namely, the dissolved oxygen was measured using a luminescent dissolved-oxygen sensor (NomaSense™ O 2 P6000, Nomacorc, Belgium), and the obtained values ranged from 1.2 to 1.9 mg/L in control wines and 1.9 to 2.6 mg/L in pressurized red and white wines, respectively. As already presented in our previous work, the total and free SO 2 were also determined by potentiometry using a sulfur dioxide measurement device (LDS Sulfilyser, Laboratories Dujardin-Salleron, Noizay, France), and the results showed 20 and 10 mg/L of total and free SO 2 in pressurized and control red wines, as well as 70 and 25 mg/L of total and free SO 2 in pressurized and control white wines, respectively [ 29 ]. Figure 1 shows a schematic diagram of experimental variables applied during HHP treatment of the wines.…”
Section: Methodsmentioning
confidence: 97%
See 4 more Smart Citations
“…Namely, the dissolved oxygen was measured using a luminescent dissolved-oxygen sensor (NomaSense™ O 2 P6000, Nomacorc, Belgium), and the obtained values ranged from 1.2 to 1.9 mg/L in control wines and 1.9 to 2.6 mg/L in pressurized red and white wines, respectively. As already presented in our previous work, the total and free SO 2 were also determined by potentiometry using a sulfur dioxide measurement device (LDS Sulfilyser, Laboratories Dujardin-Salleron, Noizay, France), and the results showed 20 and 10 mg/L of total and free SO 2 in pressurized and control red wines, as well as 70 and 25 mg/L of total and free SO 2 in pressurized and control white wines, respectively [ 29 ]. Figure 1 shows a schematic diagram of experimental variables applied during HHP treatment of the wines.…”
Section: Methodsmentioning
confidence: 97%
“…As already presented in our previous work [ 29 ], the concentrations of dissolved oxygen, total and free SO 2 were also controlled at the point of bottling and during 12 months of aging. As previously mentioned in Section 2.1 ., we used the same analytical methods and the results showed that the initial levels of dissolved oxygen at bottling in red wine amounted up to 2.2 mg/L in both pressurized and control wines, while after 12 months the levels were in the range from 0.4 to 0.6 mg/L.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations